1992
DOI: 10.5935/0305-7518.19920025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four semi-syntheticMycobacterium lepraeantigens with sera from healthy populations in endemic and non-endemic areas

Abstract: In order to determine the frequency of occurrence of antibodies to semisynthetic antigens of My cobacterium leprae in clinically healthy nonpatient populations and to establish a 'baseline' for comparison with antibody frequen cies in both patients with a history of leprosy and their contacts, ELISAs were conducted using representative sera from two areas: a leprosy endemic area, Cebu City, Philippines and a nonendemic area for leprosy Chicago, Illinois, USA. These sera were tested, by an indirect IgM ELISA, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Since early studies showed that the carbohydrates of the PGL‐I antigen are critical for its binding to antibodies, a series of neoglycoconjugate antigens containing carbohydrate epitopes of PGL‐I were prepared and were found to give a strong correlation with the native antigen in terms of detecting antibodies [12–14]. Currently, neoglycoconjugate antigens such as ND‐ O ‐BSA and ND‐ P ‐BSA are widely used for detecting anti‐PGL‐I antibodies [13,15]. Organic synthesis of the terminal disaccharides, 3,6‐di‐ O ‐Me‐Glc‐(1→ 4)‐2,3‐di‐ O ‐Me‐Rha, and the linking of this sugar to BSA carrier protein is, however, a tedious process requiring more than 20 steps [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since early studies showed that the carbohydrates of the PGL‐I antigen are critical for its binding to antibodies, a series of neoglycoconjugate antigens containing carbohydrate epitopes of PGL‐I were prepared and were found to give a strong correlation with the native antigen in terms of detecting antibodies [12–14]. Currently, neoglycoconjugate antigens such as ND‐ O ‐BSA and ND‐ P ‐BSA are widely used for detecting anti‐PGL‐I antibodies [13,15]. Organic synthesis of the terminal disaccharides, 3,6‐di‐ O ‐Me‐Glc‐(1→ 4)‐2,3‐di‐ O ‐Me‐Rha, and the linking of this sugar to BSA carrier protein is, however, a tedious process requiring more than 20 steps [13].…”
Section: Introductionmentioning
confidence: 99%